Respuesta :

Answer:

[tex] - 18.4[/tex]

Step-by-step explanation:

The given expresion is

[tex] - 9.2(4 - x)[/tex]

We want to evaluate this expression for x=2.

We substitute x=2 into the expression.

This means that, we will put 2 wherever we see x in the given expresion.

This will give us:

[tex] - 9.2(4 - 2)[/tex]

Simplify the parenthesis

[tex] - 9.2(2)[/tex]

[tex] = - 18.4[/tex]

Answer:

-18.4

Step-by-step explanation:

-9.2(4 – x)

Let x=2

-9.2(4 – 2)

Parentheses first

-9.2(2)

Multiply

-18.4

ACCESS MORE